111k views
3 votes
___cosb= 1/2(cosb(a+b)+cos(a-b)

User Mejonzhan
by
4.9k points

2 Answers

1 vote

Answer:

cos a

Explanation:

apex

User Duanne
by
5.4k points
2 votes

Answer:

Cos(a)

cos(a)*cos(b)=(1/2) (cos(a+b)+cos(a-b))

Explanation:

First we need to remember that

cos(a+b)=cos(a)*cos(b)-sen(a)*sen(b) eq.1

cos(a-b)=cos(a)*cos(b)+sen(a)*sen(b) eq.2

If we sum eq.1 with eq.2 we have:

cos(a+b)+cos(a-b)= 2 cos(a)*cos(b)

By solving we have the following

cos(a)*cos(b)= [cos(a+b)+cos(a-b)] *(1/2)

Thus, by comparing, we have our desire answer

User Vdenotaris
by
6.0k points